Structure, spectroscopic signatures, and formation of hydroxy-azirine: a potential interstellar prebiotic molecule. Issue 2 (19th January 2023) - Redondo, Pilar; Sanz-Novo, Miguel; Barrientos, Carmen; Largo, Antonio
ABSTRACT: Hydroxy-azirine (C2 H3 NO) is a -OH derivative of azirine (C2 H3 N), molecule that has been the subject of several unfruitful searches in space. Hydroxy-azirine is an isomer of the detected prebiotic species methyl isocyanate, CH3 NCO, and glycolonitrile, HOCH2 CN, as well as the yet undetected imine acetaldehyde, NHCHCHO. However, the lack of preliminary spectroscopic data on hydroxy-azirine has prevented its astronomical search. The aim of this study is to provide high-level theoretical spectroscopic signatures of the most stable hydroxy-azirine isomers to enable their eventual interstellar search. A total of 12 isomers have been characterized for hydroxy-azirine and their isomerization processes have been analysed at the CCSD(T)-F12/cc-pVTZ-F12 level. The most stable structures are 3-hydroxy-2H-azirine (I) and 2-hydroxy-2H-azirine (II) in their syn - and anti -configurations, which are suggested as the most relevant candidates for laboratory and interstellar detection. To ease their identification by means of rotational spectroscopy, we report a set of the required spectroscopic parameters using state-of-the-art composite and coupled-cluster approaches. For astronomical purposes, we provide a complete line list for I- syn and I- anti hydroxy-azirine up to 50 GHz, which takes the hyperfine structure into account, and will be essential to hunt for these interstellar candidates experimentally. In addition, anharmonic vibrational frequencies and intensities are reported to predict a trustworthy vibrational spectra and to estimate the vibrational partition function. Finally, we analyse the possibility of formation of hydroxy-azirine from the reaction of azirine with the hydroxyl radical in the gas-phase and on the surface of ices, finding for the latter a feasible formation route under interstellar conditions.